(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Background: It is important to develop orbital hydrogel implants capable of depositing drugs (particularly, antimicrobial and anticancer drugs). Purpose: To assess antimicrobial effects of hybrid hydrogel implants containing gold nanoparticles and albucide and developed for reconstructive surgery in the orbit and periorbital area. Material and Methods: A 30% aqueous solution of albucide was used in the study. Antimicrobial activity of synthesized hydrogels was determined using Escherichia coli ATCC 25922, Enterococcus faecalis ATCC 29213, Staphylococcus aureus ATCC 25923 and Pseudomonas aeruginosa ATCC 27853 strains. Results: All the synthesized samples of orbital hydrogel implants were sterile. The synthesized hydrogels and hydrogel nanocomposites with incorporated Au nanoparticles demonstrated bacteriostatic effects against E. Coli ATCC 25922, E. Faecalis ATCC 29213, and S. Aureus ATCC 25923 strains, and bactericidal effects against P. Aeruginosa ATCC 27853 strain. This study also demonstrated marked bactericidal effects of hybrid hydrogel implants incorporating both Au nanoparticles and albucide. Conclusion: Orbital hydrogel implants were found to be sterile after being sealed into polypropylene bags and steam sterilized at 121 °C for 20 minutes. Our findings of bacteriostatic and bactericidal effects of the synthesized hydrogels and hydrogel nanocomposites containing Au nanoparticles and albucide against bacterial strains of interest will allow for the absence of, or low probability of bacterial contamination in applications of these hydrogels in implants.